2017
DOI: 10.21273/hortsci12136-17
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Spur Leaves, Bourse Leaves, and Fruit on Local Flower Formation in Apple: An Approach to Understanding Biennial Bearing

Abstract: Lack of consistent flower formation is the underlying cause of biennial bearing. Flower formation in apple (Malus ×domestica Borkh.) has been associated with different factors, such as leaf area, shoot growth, bourse length, crop load, and seed number. However, it is unclear how these different factors interact to promote or inhibit flower formation. The effect of spur defoliation, fruit removal, and their interaction were evaluated on spur flower f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…This highlights the very biennial nature of 'Honeycrisp' and may have been due to the time of thinning (petal fall), as earlier blossom thinning has been shown to be more effective at promoting return bloom than later thinning as practiced here (Tromp, 2000). Two major flower formation inhibitors have been previously described in apple: GAs (Marino and Greene 1981;McArtney and Li, 1998;McLaughlin and Greene, 1984) and defoliation (Elsysy and Hirst 2017;Fulford, 1960;Harley et al, 1942). In most of these previous studies, treatments were applied either on whole trees or to major branches.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This highlights the very biennial nature of 'Honeycrisp' and may have been due to the time of thinning (petal fall), as earlier blossom thinning has been shown to be more effective at promoting return bloom than later thinning as practiced here (Tromp, 2000). Two major flower formation inhibitors have been previously described in apple: GAs (Marino and Greene 1981;McArtney and Li, 1998;McLaughlin and Greene, 1984) and defoliation (Elsysy and Hirst 2017;Fulford, 1960;Harley et al, 1942). In most of these previous studies, treatments were applied either on whole trees or to major branches.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to leaf area, the types of leaves are also important for flower formation. Our recent work showed that bourse leaves, but not spur leaves, were important in the regulation of flower formation in apple (Elsysy and Hirst, 2017). Moreover, the effect of local inhibitions such as fruiting and defoliation could be affected by the availability of flowering promotion signals in the whole tree (Elsysy and Hirst, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It influences many physiological processes in fruit orchards such as source-sink carbon relationships, water status and water consumption (Bustan et al, 2016). The fruit are strong carbohydrate sink, and high crop load levels can stunt the vegetative growth (Yuri et al, 2011) and return bloom of trees (Elsysy and Hirst, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Biennial bearing is ''the fluctuation in cropping from year-to-year caused by irregular flowering'' (Hirst, 2017). Considerable research has been conducted to investigate biennial bearing; however, it remains a complicated problem (Bangerth, 2009;Elsysy and Hirst, 2017;Monselise and Goldschmidt, 1982). A number of highvalue apple cultivars exhibit biennial bearing, including Cameo, Fuji, and Honeycrisp.…”
mentioning
confidence: 99%